Syntheses and Applications of 2‐Alkynylnitriles. Issue 11 (25th October 2019) - Bhatt, Divya; Kumari, Chandresh; Goswami, Avijit
Abstract: 2‐Alkynylnitriles are a distinguished class of molecules known to play a pivotal role in the construction of a plethora of carbo‐/heterocyclic compounds of biological and pharmaceutical importance. These molecules have been exploited as hydrolytically stable irreversible labels for cysteine tagging. In addition, they also form an important homologous series of complex interstellar molecules identified by radioastronomy. Therefore, in this Minireview, we highlight the numerous transformations and diverse reactions carried out with these substrates. Different reactions including nucleophilic additions and various carbo‐/heterocycles formation are the prime focal areas of this article. Mechanistic aspects for certain reactions have also been delineated. Abstract : 2‐Alkynylnitriles possessing both nitrile and acetylene functionalities are versatile synthons and have been utilized for the synthesis of a number of carbo‐ and other heterocyclic compounds. The main focus of this minireview is to highlight the various transformations and diverse reactions carried out using these substrates primarily nucleophilic additions and carbo‐/heterocycles formation.